Vaccine Induced Acute Transverse Myelitis: A Case Report - Chandra, Avinash; Rajbhandari, Reema; Acharya, Samir; Gurung, Priya; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Acute transverse myelitis is a focal infl ammatory disorder of the spinal cord. One of the main etiologic factors include, multiple sclerosis, post-infectious and post-traumatic events although autoimmune phenomenon is the most common cause. Transverse Myelitis (TM) due to etiology other than Multiple Sclerosis has shown spinal cord involvement of two or more segments. Annually millions of active immunization with vaccines is carried out globally with few transverse myelitis caused because of the adverse reactions due to these vaccinations. In order to improve accuracy of reporting, research and diagnosis, the Transverse Myelitis Consortium Working Group (TMCWG) have produced criteria for the diagnosis of ATM. Here we report a case of TM in adult, diagnosed as TM consistent with the TMCWG criteria and probably this is the first ever been reported case from Nepal. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 89-91